Peramalan Produk Domestik Regional Bruto (PDRB) Provinsi Bali Triwulanan (Q-to-Q) Tahun Dasar 2010 dengan Model Arima - Wellyanti, Briliana (Jurnal Ekonomi Kuantitatif Terapan, 2019)
Gross Regional Domestic Product (GDRP) is one indikator of the progress of an area / region. Economic growth is a comparison of the GDRP in the current period against the previous period. In the planning area (RPJMD), local governments need economic growth forecast in the next 5 years. In this case the GDRP forecast may be obtained by various methods, one of the methods that will be addressed in this study is the GDRP forecast Bali using ARIMA. Bali’s GDRP on First Quarter of 2007 to the second quarter of 2016 is obtained from Statistik Bali. The analytical method used is the analysis of time series data that ARIMA models. The results showed that the ARIMA model is able to predict the GDP Bali until the fourth quarter 2018. The best ARIMA model is ARIMA (3,1,0).
Keywords: PDRB, Peramalan PDRB, ARIMA, Time series Analysis